Ovid's Erotic Poems : "Amores" and "Ars Amatoria" - Ovid, 43 B.C.-17 A.D. or 18 A.D (Book collections on Project MUSE., 2014)
Translated by award-winning poet Len Krisak, Ovid's Erotic Poems offers a fresh modern take on the renowned Roman's sophisticated satirical verse on love, sex, marriage, and adultery.